Hodnocení finanční situace společnosti a návrhy na její zlepšení - Coufal, Denis (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Bakalářská práce se věnuje hodnocení finanční situace sledované společnosti v období let 2014 až 2018 a návrhům na její zlepšení. Teoretická část vymezuje pojmy a definuje ukazatele finanční analýzy. Praktická část používá metody uvedené v předešlé části a provádí výpočty jednotlivých ukazatelů. Závěrečná část práce předkládá návrhy a doporučení na zlepšení finanční situace společnosti.

The purpose of this bachelor‘s thesis is the evaluation of the financial situation in the selected company in the period from 2014 to 2018 and proposals to its improvements. The theoretical part defines concepths of financial analysis and financial ratios. The practical part puts methods from the previous part in use and calculates individual financial ratios. The final part presents proposals and recommendations to improve the financial situation of the selected company.
Evaluation of the Financial Situation in the Company and Proposals to its improvement
Keywords: hodnocení finanční situace; finanční analýza; rentabilita; likvidita; zadluženost; aktivita; evaluation of the financial situation; financial analysis; rentability; liquidity; debt ratios; activity ratios